The Receptor Tyrosine Kinase AXL Is Required at Multiple Steps of the Metastatic Cascade during HER2-Positive Breast Cancer Progression - Marie-Anne Goyette; Stéphanie Duhamel; Léo Aubert; Ariane Pelletier; Paul Savage; Marie-Pier Thibault; Radia Marie Johnson; Peter Carmeliet; Mark Basik; Louis Gaboury; William J. Muller; Morag Park; et al. (Cell Reports, 2018)
Summary: AXL is activated by its ligand GAS6 and is expressed in triple-negative breast cancer cells. In the current study, we report AXL expression in HER2-positive (HER2+) breast cancers where it correlates with poor patient survival. Using murine models of HER2+ breast cancer, Axl, but not its ligand Gas6, was found to be essential for metastasis. We determined that AXL is required for intravasation, extravasation, and growth at the metastatic site. We found that AXL is expressed in HER2+ cancers displaying epithelial-to-mesenchymal transition (EMT) signatures where it contributes to sustain EMT. Interfering with AXL in a patient-derived xenograft (PDX) impaired transforming growth factor β (TGF-β)-induced cell invasion. Last, pharmacological inhibition of AXL specifically decreased the metastatic burden of mice developing HER2+ breast cancer. Our data identify AXL as a potential anti-metastatic co-therapeutic target for the treatment of HER2+ breast cancers. : Metastasis is responsible for the majority of breast cancer deaths. Goyette et al. report that AXL is expressed in HER2+ human tumors that acquire aggressive features. Blockade of AXL in mice decreases metastasis. These results suggest that co-targeting AXL and HER2 may limit the metastatic progression of HER2+ breast cancer. Keywords: AXL, HER2, breast cancer, metastasis, EMT, PDX, AXL inhibitor